Gastrix : a guide to gastroenterology and hepatology - Rogler, Gerhard 1963-; Bauerfeind, Peter; Fried, Michael Fried, Michael; Gubler, Christoph; Müllhaupt, Beat (Basel, Switzerland Karger, 2018)
In daily medical practice, physicians often use scores, classifications and schematic diagnostic paths to make clear and comprehensive decisions. Treatment algorithms have also proven to be effective. However, it has become increasingly difficult or even impossible to have all scores, schemata and algorithms at hand, and a search on the internet can be very time consuming. Gastrix solves this problem: unlike classic gastroenterology and hepatology textbooks, it summarizes all necessary information in the form of a pocket-sized book. Gastroenterologists will thus have all relevant information easily available at all times.
Keywords: GASTROENTEROLOGÍA -- MANUALES; HEPATOLOGÍA -- MANUALES; HEPATOLOGÍA